Seeding Intercultural Awareness through the Teaching of Indonesian Language and Literature at SMAN 3 Malang - Rozin, Muhammad; Setiawan, Fredy Nugroho; Eka, Scarletina Vidyayani (Institute of Research and Community Service, University of Brawijaya, 2022)
Indonesia is a diverse country in term of cultural, religious, ethnic, and linguistic backgrounds. With the escalation of social problems nowadays, spaces to seed the values of harmony, tolerance and cohesion must be fostered. The government through schools seeks to instill these values. One of the efforts that can be made by schools is through intercultural education which can be integrated intovarious aspects of school activities, one of which is the teaching of Indonesian Language subject. This research aims to map the extent to which the concept of intercultural education is practiced at SMAN 3 Malang. This was done by reviewing the lesson plans (RPP) and the materials used by the teachers. The results show that, in general, the lesson plans have facilitated the ideal transmission of intercultural awareness. Yet, at the practical level, the implementation of teaching and learning activities in the classroom and outside the classroom needs to be ensured according to the plan. So, it is not just ideal on paper. These results are in line with the Core Competences (KI) and Basic Competences (KD) of Indonesian language subject outlined by the Government in an effort to form the space of tolerant and harmonious Indonesian society.